High strength porous composite filter media and process for making same

CN122830202APending Publication Date: 2026-09-29TIANJIN TIANMEI ENVIRONMENTAL PROTECTION TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611208551.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-11
Publication Date
2026-09-29

AI Technical Summary

Technical Problem

实现大颗粒杂质表层拦截、微细杂质深层分级过滤

Benefits of technology

1. 本发明采用金属-无机-有机杂化四层梯度一体化烧结结构,底部金属骨架提供高力学强度,解决传统滤材受压变形、爆破、断裂缺陷;梯度贯通微孔结构实现杂质分级拦截,过滤通量提升,滤孔堵塞速率降低;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122830202A_ABST
    Figure CN122830202A_ABST
Patent Text Reader

Abstract

This invention provides a high-strength porous composite filter medium and its processing technology, which consists of a four-layer integrated sintered composite structure. From bottom to top, the four layers are a supporting base layer, a bonding composite layer, a filter layer, and a dirt-resistant protective layer. Each layer has multiple micropore channels evenly distributed within it, with adjacent layers having different pore sizes, forming a gradient-diameter micropore channel that runs vertically through the entire structure. This invention employs a metal-inorganic-organic hybrid four-layer gradient integrated sintered structure. The bottom metal skeleton provides high mechanical strength, solving the problems of deformation, bursting, and breakage inherent in traditional filter media under pressure. The gradient-through micropore structure enables graded interception of impurities, increasing filtration throughput and reducing pore clogging rate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of porous filtration functional materials technology, and in particular to high-strength porous composite filter media and their processing technology. Background Technology

[0002] Currently, commercially available porous filter media are mainly divided into three categories: organic polymer porous filter media, inorganic ceramic porous filter media, and sintered metal porous filter media. Existing materials generally have the following defects: (1) Organic polymer filter materials, such as polypropylene, polyester, PTFE filter membranes, etc., have high porosity and low filtration resistance, but poor overall structural mechanical properties, low tensile strength and burst strength. They are prone to deformation, delamination and damage under high pressure backwashing conditions; long-term operation is prone to pore collapse and filter media caking, resulting in short service life. (2) Inorganic ceramic porous filter media has excellent corrosion resistance, high temperature resistance and chemical stability, but the material is brittle, has poor impact resistance and is prone to cracking and breaking under pressure. (3) Single-layer metal sintered porous filter media has high mechanical strength and excellent high temperature resistance, but the pore size is single and the grading filtration capacity is poor; the specific surface area is small and the adsorption and interception performance is weak. Under high flow impact conditions, the local pores are easily deformed.

[0003] Therefore, there is an urgent need for a composite filter medium that combines high structural strength, gradient-level porous structure, corrosion resistance, and high-throughput filtration. Summary of the Invention

[0004] In view of the above technical problems, the present invention provides a high-strength porous composite filter medium with high structural strength and excellent filtration performance, and its processing technology.

[0005] This invention provides a high-strength porous composite filter medium and its processing technology, consisting of a four-layer integrated sintered composite structure. From bottom to top, the four layers are a supporting base layer, a bonding composite layer, a filter layer, and a dirt-resistant protective layer. Each layer contains multiple evenly distributed micropore channels, with adjacent layers having different pore sizes, forming a gradient-diameter micropore channel that runs vertically throughout the entire structure. This enables the interception of large particles on the surface and the deep, graded filtration of fine impurities.

[0006] The raw material mass ratio of the supporting base layer is 75-85 parts of 316L stainless steel spherical powder, 10-15 parts of titanium alloy porous short fiber, 3-8 parts of inorganic sintering flux powder, and 1-2 parts of antioxidant modifier; the thickness of the supporting base layer is 1.2-2.0 mm, the average pore size is 45-60 μm, and the porosity is 48%-55%; it bears the overall medium load and provides impact resistance, tensile strength, and blast resistance.

[0007] The raw material mass ratio of the bonding composite layer is 45-55 parts of irregular powder of 316L stainless steel, 25-35 parts of porous micro powder of ultrafine alumina, 10-15 parts of fluororesin modified bonding powder, and 3-5 parts of compatibility additive; the thickness of the bonding composite layer is 0.4-0.8 mm, the average pore size is 22-35 μm, and the porosity is 58%-65%; it connects the supporting base layer and the filter layer, eliminates interlayer stress, improves the overall bonding strength of the four layers, and intercepts medium-sized suspended impurities that penetrate the bottom layer.

[0008] The filter layer has the following raw material mass ratio: 40-50 parts of porous diatomaceous earth powder, 20-25 parts of nano-titanium dioxide modified powder, 15-20 parts of polyetheretherketone ultrafine powder, 8-12 parts of porous glass microsphere filler, and 2-3 parts of dispersant; the filter layer has a thickness of 0.6-1.0 mm, an average pore size of 5-15 μm, and a porosity of 70%-78%; the core solid-liquid and solid-gas separation zone relies on a high specific surface area porous structure to intercept fine suspended matter and colloidal impurities.

[0009] The raw material ratio of the antifouling protective layer is 35-45 parts of hydrophobic modified silica nanopowder, 30-40 parts of nano polytetrafluoroethylene powder, 15-20 parts of inert ceramic micro powder, and 2-4 parts of wear-resistant modifier. The thickness of the antifouling protective layer is 0.2-0.5 mm, the average pore size is 18-25 μm, and the porosity is 68%-75%. The surface is hydrophobic and antifouling, resistant to acid and alkali corrosion, prevents impurities from adhering and scaling on the filter pore surface, reduces filtration operating resistance, and improves backwashing regeneration efficiency.

[0010] This invention provides a high-strength porous composite filter medium, characterized in that the processing technology of the filter medium includes the following specific steps: S1: Raw material pretreatment modification Weigh the powder raw materials according to the formula of each layer, put them into a high-speed vortex mixer, add the corresponding additives layer by layer, and stir and mix at a constant temperature of 65~75℃ for 45~60 minutes. After mixing, pass the mixture through a 120-mesh standard vibrating screen to remove large agglomerated powder particles. Vacuum dry the sieved powder at a vacuum degree of -0.09~-0.1MPa, a drying temperature of 80℃, and a holding time of 2 hours to remove free moisture and volatile impurities from the raw materials. S2: Mold pretreatment and demolding coating spraying High-temperature resistant, high-purity graphite molding mold is used. The inner cavity of the mold is polished to a mirror surface roughness Ra≤0.8μm. The inner cavity is uniformly sprayed with a high-temperature resistant boron nitride release coating with a thickness of 20~30μm and cured at 120℃ for 30min. S3: Layered Precision Powder Spreading and Shaping Following the bottom-up structural sequence, four layers of pre-treated powder are laid in the mold cavity in a step-by-step, quantitative manner. After each layer of powder is laid, a vibration compaction process is adopted with a vibration frequency of 35Hz and a vibration compaction time of 15s to ensure uniform pores and a flat surface in a single layer. The thickness error of each layer of powder is strictly controlled to be ≤±0.05mm, forming a four-layer composite powder blank. S4: Segmented Stepped Low-Temperature Integrated Sintering The composite billet along with the mold is sent into a vacuum sintering furnace. An inert nitrogen protective atmosphere is used to prevent high-temperature oxidation of the metal raw materials. A three-stage stepped heating and heat preservation program is set. S5: Gradient slow cooling for shaping After sintering, a gradient slow cooling process is adopted in the furnace. First, the temperature is reduced to 400℃ at a cooling rate of 2℃ / min, and then naturally cooled to room temperature with the furnace. S6: Post-processing finishing Edges and corners are laser-cut, surfaces are ground and leveled, and internal residual micro-powder blocking the pores is removed by high-pressure pure water bidirectional rinsing. The pore connectivity rate is tested under vacuum, and after sampling and mechanical property testing, the products are packaged and stored.

[0011] The three-stage stepped temperature rise protection procedure specifically includes the following steps: First stage of heating: The room temperature is increased to 260℃ at a rate of 4℃ / min and held for 40min to remove trace amounts of residual additives and internal gases from the green body; The second stage of heating: the temperature is increased to 480~520℃ at a rate of 3.5℃ / min and held for 90min to complete the melting and cross-linking of organic and inorganic powders in the surface and functional layers; The third stage of heating: the temperature is increased to 680~720℃ at a rate of 2.5℃ / min and held for 120min to achieve metallurgical fusion bonding between the supporting base layer and the bonding transition layer.

[0012] The beneficial effects of this invention are as follows: 1. This invention adopts a metal-inorganic-organic hybrid four-layer gradient integrated sintering structure. The bottom metal skeleton provides high mechanical strength, solving the defects of traditional filter materials such as deformation, bursting, and breakage under pressure. The gradient through-hole microporous structure realizes the graded interception of impurities, improves the filtration throughput, and reduces the filter pore clogging rate. 2. The hybrid composite material system of the present invention takes into account hydrophobicity, antifouling properties, resistance to strong acids and alkalis, and high temperature resistance. It can be adapted to complex filtration conditions such as chemical strong acid and strong alkali filtrate, high temperature flue gas, and high turbidity industrial wastewater, and has a wide range of applicable scenarios. 3. This invention adopts a segmented, stepped low-temperature sintering process, which reduces energy consumption compared to traditional high-temperature sintering, is suitable for large-scale industrial production lines, has lower overall production and equipment costs, and has excellent media regeneration performance. The initial filtration flux can be restored with simple high-pressure backwashing, extending the service life and reducing the operation and maintenance costs of filtration equipment and the cost of replacing consumables. Attached Figure Description

[0013] Figure 1 This is a process flow diagram of the present invention. Detailed Implementation

[0014] The technical solution of the present invention will now be clearly and completely described with reference to the accompanying drawings. Obviously, the described embodiments are only some, not all, of the embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0015] In the description of this invention, it should be noted that the terms "center," "upper," "lower," "left," "right," "vertical," "horizontal," "inner," and "outer," etc., indicate the orientation or positional relationship based on the orientation or positional relationship shown in the accompanying drawings. They are used only for the convenience of describing the invention and for simplifying the description, and do not indicate or imply that the device or element referred to must have a specific orientation, or be constructed and operated in a specific orientation. Therefore, they should not be construed as limitations on the invention. Furthermore, the terms "first," "second," and "third" are used for descriptive purposes only and should not be construed as indicating or implying relative importance.

[0016] In the description of this invention, it should be noted that, unless otherwise explicitly specified and limited, the terms "installation," "connection," and "linking" should be interpreted broadly. For example, they can refer to a fixed connection, a detachable connection, or an integral connection; they can refer to a mechanical connection or an electrical connection; they can refer to a direct connection or an indirect connection through an intermediate medium; and they can refer to the internal connection of two components. Those skilled in the art can understand the specific meaning of the above terms in this invention based on the specific circumstances. Furthermore, the technical features involved in the different embodiments of this invention described below can be combined with each other as long as they do not conflict with each other. Example 1

[0017] The technical solution of the present invention will now be clearly and completely described with reference to the accompanying drawings.

[0018] Optimal quality formulation for each functional layer: Supporting substrate: 80 parts 316L stainless steel powder, 12 parts titanium alloy short fibers, 6 parts sintering flux powder, 2 parts antioxidant; thickness 1.6mm, pore size 52μm, porosity 52%; Adhesive composite layer: 50 parts stainless steel powder, 32 parts alumina micro powder, 13 parts fluororesin adhesive powder, 5 parts compatibility additive; thickness 0.6 mm, pore size 28 μm, porosity 62%; Filter layer: 45 parts diatomaceous earth powder, 22 parts nano titanium dioxide, 18 parts PEEK powder, 12 parts porous glass microspheres, 3 parts dispersant; thickness 0.8 mm, pore size 10 μm, porosity 74%; Stain-resistant protective layer: 40 parts hydrophobic silica, 35 parts PTFE nanopowder, 21 parts ceramic micro powder, and 4 parts wear-resistant additive; thickness 0.35 mm, pore size 22 μm, porosity 71%. Example 2

[0019] The four layers of raw materials from Example 1 were respectively fed into four sets of independent high-speed vortex mixers. The constant temperature water bath was set to 70°C, and the mixture was stirred at high speed in a closed environment for 50 minutes at a stirring speed of 1800 r / min. After mixing, the mixture was sieved through a 120-mesh stainless steel vibrating screen to remove powder agglomerates. The qualified powder was transferred to a vacuum oven and dried at a vacuum of -0.095 MPa and a constant temperature of 80°C for 2 hours to remove adsorbed water vapor and low molecular weight volatiles. The powder was then cooled, sealed, and stored for later use.

[0020] A high-purity isostatic graphite rectangular molding die was selected, with a molding cavity size of 300mm×300mm. The inner cavity working surface was machined to a mirror roughness Ra=0.6μm by mechanical grinding. A hexagonal boron nitride high-temperature release coating was uniformly sprayed using a low-pressure spray gun, and the dry film coating thickness was controlled to 25μm. The coating was cured at a constant temperature of 120℃ in a hot air oven for 30 minutes and then cooled for later use.

[0021] Following a bottom-up forming sequence, the powder is laid in layers using a CNC automatic powder spreading device: the bottom layer is a supporting base powder with a target forming thickness of 1.6mm and a powder thickness error controlled within ±0.04mm; after each layer is laid, an electromagnetic vibration compaction platform is activated with a fixed vibration frequency of 35Hz and a single compaction time of 15s to ensure uniform pore distribution in the powder blank; the 0.6mm transition layer, 0.8mm filter functional layer, and 0.35mm stain-resistant surface layer are laid in sequence without intermediate sintering, forming a four-layer composite powder blank in one step; after forming, the average pore size and preset porosity of each layer are tested, and if they meet the structural parameters of Example 1, the process is transferred to the sintering process.

[0022] The integral composite powder preform, along with the graphite mold, is fed into a programmable vacuum sintering furnace. After the furnace is closed, a vacuum is drawn to -0.098 MPa, and high-purity nitrogen is introduced to replace the air inside the furnace, maintaining a slightly positive pressure inert protective atmosphere. The three-stage stepped sintering program is then initiated. Degassing and heating stage: The room temperature is raised to 260℃ at a uniform rate of 4℃ / min, and the temperature is kept constant for 40min to remove residual dispersant, coupling agent and trapped air from the green body; Hybrid crosslinking stage: The temperature is increased to 500℃ at a rate of 3.5℃ / min and held at a constant temperature for 90min to complete the melt crosslinking and curing of the surface PTFE, functional layer PEEK organic powder and inorganic filler; Metallurgical composite stage: The temperature is raised to 700℃ at a rate of 2.5℃ / min and held at a constant temperature for 120min to achieve low-temperature metallurgical fusion between stainless steel powder layers, forming an integrated billet with four layers.

[0023] S5: Gradient slow cooling for shaping After the sintering and heat preservation stage is completed, the intelligent gradient slow cooling program in the furnace is started: the temperature is cooled to 400℃ at a fixed cooling rate of 2℃ / min to eliminate the internal stress of temperature difference in the multi-layer composite billet; the temperature control system is turned off and the billet is allowed to cool naturally to room temperature with the furnace. The furnace is prohibited from being opened for rapid cooling throughout the process to prevent the plate from warping and interlayer micro-cracks.

[0024] After natural cooling, the integrated composite filter media blank is directly demolded and removed; the four sides and corners are trimmed using a fiber laser cutting machine, and the surface is finely ground and leveled on both sides using a surface grinder; it is rinsed with 0.15MPa high-pressure pure water in both directions for 30 minutes to remove residual micro-powder that clogs the pores; the pore connectivity, mechanical properties and filtration flux of the medium are tested.

[0025] The measured indicators of the finished product in this process embodiment are as follows: overall tensile strength 20.6 MPa, burst pressure 2.92 MPa, flexural strength 23.5 MPa; pure water filtration flux 915 L / (m²·h·0.1 MPa); no structural corrosion after long-term immersion in acidic and alkaline media with pH 3~12; interlayer peeling rate 0.65% after 50 high-pressure backwashes; finished product dimensional consistency error <0.1 mm; batch preparation yield 97.2%.

[0026] The foregoing has shown and described the basic principles, main features, and advantages of the present invention. The various components mentioned in this invention are common technologies in the existing field. Those skilled in the art should understand that the present invention is not limited to the above embodiments. The embodiments and descriptions in the specification are merely illustrative of the principles of the invention. Various changes and modifications can be made to the invention without departing from its spirit and scope, and all such changes and modifications fall within the scope of the present invention as claimed. The scope of protection of this invention is defined by the appended claims and their equivalents.

Claims

1. A high-strength porous composite filter medium, characterized in that... Composed of a four-layer integrated sintered composite structure, the four layers are, in order from bottom to top, a supporting base layer, an adhesive composite layer, a filter layer, and a dirt-resistant protective layer. Each layer has multiple microporous channels evenly distributed inside, and the pore size of the microporous channels in adjacent layers is different, forming a gradient variable diameter microporous channel that runs through the whole structure from top to bottom.

2. The high-strength porous composite filter medium according to claim 1, characterized in that... The raw material mass ratio of the supporting base layer is 75-85 parts of 316L stainless steel spherical powder, 10-15 parts of titanium alloy porous short fiber, 3-8 parts of inorganic sintering flux powder, and 1-2 parts of antioxidant modifier. The raw material mass ratio of the adhesive composite layer is 45-55 parts of irregular powder of 316L stainless steel, 25-35 parts of porous micro powder of ultrafine alumina, 10-15 parts of fluororesin modified adhesive powder, and 3-5 parts of compatibility additive. The raw material composition of the filter layer is as follows: 40-50 parts of porous diatomaceous earth powder, 20-25 parts of nano-titanium dioxide modified powder, 15-20 parts of polyether ether ketone ultrafine powder, 8-12 parts of porous glass microsphere filler, and 2-3 parts of dispersant. The raw material ratio of the antifouling protective layer is 35-45 parts of hydrophobic modified silica nanopowder, 30-40 parts of nano polytetrafluoroethylene powder, 15-20 parts of inert ceramic micro powder, and 2-4 parts of wear-resistant modifying additive.

3. The high-strength porous composite filter medium according to claim 2, characterized in that... The supporting base layer has a thickness of 1.2~2.0mm, an average pore size of 45~60μm, and a porosity of 48%~55%; the adhesive composite layer has a thickness of 0.4~0.8mm, an average pore size of 22~35μm, and a porosity of 58%~65%; the filter layer has a thickness of 0.6~1.0mm, an average pore size of 5~15μm, and a porosity of 70%~78%; and the dirt-resistant protective layer has a thickness of 0.2~0.5mm, an average pore size of 18~25μm, and a porosity of 68%~75%.

4. The high-strength porous composite filter medium according to any one of claims 1-3, characterized in that... The processing technology of this filter medium includes the following specific steps: S1: Weigh the powder raw materials according to the formula of each layer, put them into the high-speed vortex mixer, add the corresponding additives layer by layer, and stir and mix at a constant temperature of 65~75℃ for 45~60 minutes; after mixing, pass through a 120-mesh standard vibrating screen to remove large agglomerated powder particles; vacuum dry the sieved powder at a vacuum degree of -0.09~-0.1MPa, drying temperature of 80℃, and heat preservation for 2 hours to remove free moisture and volatile impurities inside the raw materials; S2: High-temperature resistant, high-purity graphite molding mold is used. The inner cavity of the mold is polished to a mirror surface roughness Ra≤0.8μm. The inner cavity is uniformly sprayed with a high-temperature resistant boron nitride release coating with a thickness of 20~30μm and cured at 120℃ for 30min. S3: Following the bottom-up structural sequence, four layers of pre-treated powder are laid in the mold cavity in steps and quantities; after each layer of powder is laid, a vibration compaction process is adopted with a vibration frequency of 35Hz and a vibration compaction time of 15s to ensure uniform pores and flat surface of the single layer; the thickness error of each layer of powder is strictly controlled to be ≤±0.05mm to form a four-layer composite powder blank; S4: The composite billet along with the mold is sent into the vacuum sintering furnace. An inert nitrogen protective atmosphere is used to prevent high-temperature oxidation of the metal raw materials. A three-stage stepped heating and heat preservation program is set. S5: After sintering, a gradient slow cooling process is adopted in the furnace. First, the temperature is reduced to 400℃ at a cooling rate of 2℃ / min, and then naturally cooled to room temperature with the furnace. S6: Edges and corners are laser-cut, surfaces are ground and leveled, high-pressure pure water is used for bidirectional rinsing to remove residual micro-powder blocking the pores, pore connectivity is tested under vacuum, and mechanical properties are sampled and then packaged and stored.

5. The high-strength porous composite filter medium according to claim 4, characterized in that... The three-stage stepped temperature rise protection procedure specifically includes the following steps: First stage of heating: The room temperature is increased to 260℃ at a rate of 4℃ / min and held for 40min to remove trace amounts of residual additives and internal gases from the green body; The second stage of heating: the temperature is increased to 480~520℃ at a rate of 3.5℃ / min and held for 90min to complete the melting and cross-linking of organic and inorganic powders in the surface and functional layers; The third stage of heating: the temperature is increased to 680~720℃ at a rate of 2.5℃ / min and held for 120min to achieve metallurgical fusion bonding between the metal base layer and the transition layer.